Optimization of instant sweet osmanthus white tea: formulation, sensory evaluation, and antioxidant properties - Yang, Yuhua; Fan, Li; Lin, Yiqin; Huang, Yan; Zhang, Jianming; Li, Shaohua; Ma, Chunhua; Cheng, Xi; Koh, Wee Yin; Tan, Thuan-Chew (Frontiers in Nutrition, 2025)
ObjectiveThis study aims to optimize the formulation of instant sweet osmanthus white tea (IOWT) and evaluate its antioxidant activities through in vitro assays.MethodsSingle-factor and orthogonal experiments were conducted to investigate the impacts of sweet osmanthus-to-white tea ratio and the concentrations of β-cyclodextrin, erythritol, and citric acid on sensory properties and total flavonoids content (TFC) of IOWT. Mixtures of the dried ingredients were spray-dried to produce IOWT.Results and discussionThe optimal formulation of IOWT was as follows: sweet osmanthus-towhite tea ratio of 1:5, 4% β-cyclodextrin, 6% erythritol, and 0.5% citric acid. This optimized IOWT formulation obtained the highest sensory score of 89.5 and a TFC of 25.76%. Using ascorbic acid as a positive control, the in vitro antioxidant activities of the optimized IOWT formulation were assessed by measuring its ability to scavenge DPPH radicals, hydroxyl radicals, superoxide anion radicals, and ABTS radicals. At a concentration of 1.0 mg/mL, the optimized IOWT formulation exhibited scavenging rates of 88.01, 94.99, 97.57, and 99.11% against DPPH, hydroxyl radicals, superoxide anion radicals, and ABTS radicals, respectively, indicating strong in vitro antioxidant activities of IOWT. This study demonstrated promising potential for the development of novel white tea-based products.